Revisiting the Rule of Optimism. - Kettle, Martin; Jackson, Sharon (British Journal of Social Work, 2017)
The 'rule of optimism' has been a key feature of child protection discourse in the UK since being introduced as a theoretical construct over thirty years ago. It has continuously been drawn upon to explain professional action and has been most notably utilised as a powerful explanatory device within Serious Case Reviews (SCRs). Yet, despite its longevity, the deployment of the construct has been subject to very little critique. This paper seeks to redress that balance and will explore how 'the rule' as an explanatory device has become rearticulated and repositioned as an individualising psychological construct which has almost invariably focused attention on the practices of individual social workers at the expense of an analysis of the structural conditions which frame these practices. In doing so, this paper traces the origins of the rule and explores the integrity and thrust of contemporary applications. Evidence from recent SCRs will be drawn upon to suggest that 'the rule', albeit in its psychologically distilled form, retains currency. Drawing on the work of Berlant, 'the rule of optimism' will be reconsidered alongside an exploration of the 'role of optimism'.